Adaptive servoventilation versus oxygen therapy for sleep disordered breathing in patients with heart failure: a randomised trial. Issue 1 (31st March 2016) - Murase, Kimihiko; Ono, Koh; Yoneda, Tomoya; Iguchi, Moritake; Yokomatsu, Takafumi; Mizoguchi, Tetsu; Izumi, Toshiaki; Akao, Masaharu; Miki, Shinji; Nohara, Ryuji; Ueshima, Kenji; Mishima, Michiaki; et al.
Abstract : Background: Both adaptive servoventilation (ASV) and nocturnal oxygen therapy improve sleep disordered breathing (SDB), but their effects on cardiac parameters have not been compared systematically. Methods and results: 43 patients with chronic heart failure (CHF; left ventricular ejection fraction (LVEF) ≤50%) with SDB were randomly assigned to undergo ASV (n=19, apnoea hypopnoea index (AHI)=34.2±12.1/h) or oxygen therapy (n=24, 36.9±9.9/h) for 3 months. More than 70% of SDB events in both groups were central apnoeas or hypopnoeas. Although nightly adherence was less for the ASV group than for the oxygen group (4.4±2.0 vs 6.2±1.8 h/day, p<0.01), the improvement in AHI was larger in the ASV group than in the oxygen group (−27.0±11.5 vs −16.5±10.2/h, p<0.01). The N -terminal pro-brain natriuretic peptide (NT-proBNP) level in the ASV group improved significantly after titration (1535±2224 to 1251±2003 pg/mL, p=0.01), but increased slightly at follow-up and this improvement was not sustained (1311±1592 pg/mL, p=0.08). Meanwhile, the level of plasma NT-proBNP in the oxygen group did not show a significant change throughout the study (baseline 1071±1887, titration 980±1913, follow-up 1101±1888 pg/mL, p=0.19). The significant difference in the changes in the NT-proBNP level throughout the study between the 2 groups was not found (p=0.30). Neither group showed significant changes in echocardiographic parameters. Conclusions: Although ASV produced better resolution of SDB in patients with CHF as compared with oxygen therapy, neither treatment produced a significant improvement in cardiac function in the short term. Although we could not draw a definite conclusion because of the small number of participants, our data do not seem to support the routine use of ASV or oxygen therapy to improve cardiac function in patients with CHF with SDB. Trial registration number: NCT01187823 (http://www.clinicaltrials.gov).